Supported copper-based catalyst as well as preparation and application thereof in nitrobenzene hydrogenation

Through the preparation method of the supported copper-based catalyst, the existing problems of low catalyst activity, high cost and low low temperature reaction activity are solved, and high activity and low cost catalyst preparation is achieved, and the ability to catalyze the hydrogenation of nitrobenzene to form aniline is highly selectively.

CN119771405AActive Publication Date: 2025-04-08DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311290254.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The catalysts used in the preparation of aniline by hydrogenation of nitrobenzene are relatively low in activity, are too high in cost, and are low in reaction activity at low temperatures.

Method used

Using the preparation method of a supported copper-based catalyst, the copper salt solution is impregnated on metal oxide A, and dried and calcined in a constant temperature oven, followed by reduction treatment in a hydrogen atmosphere, and finally another metal oxide B is added to the organic solvent, and heat treatment is carried out to obtain the supported copper-based catalyst.

Benefits of technology

The migration of copper species between different metal oxides at low temperatures is achieved, and a high-active, low-cost supported copper-based catalyst is prepared, with the ability to catalyze the hydrogenation of nitrobenzene to form aniline with high selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771405A_ABST
    Figure CN119771405A_ABST
Patent Text Reader

Abstract

The invention discloses a supported copper-based catalyst as well as preparation and application thereof. Comprising the following steps: preparing a copper salt solution; adding a copper salt solution into the metal oxide carrier to achieve equivalent-volume impregnation; and after drying, roasting in a muffle furnace at 300-500 DEG C for 2-12 hours. Carrying out reduction treatment on the obtained solid for 1-4 hours at 200-400 DEG C in a hydrogen atmosphere, and then putting the solid into an organic solution; adding another metal oxide carrier into the solution, and heating the mixed solution to 100-170 DEG C; and centrifugally washing to obtain the supported copper-based catalyst. The preparation method disclosed by the invention can realize the migration of copper species among different metal oxides at low temperature to obtain supported copper-based catalysts with different dispersity and electronic states. The invention provides the application of the prepared supported copper-based catalyst in nitrobenzene hydrogenation, and the supported copper-based catalyst has high activity and high selectivity. The preparation method is simple, low in cost and beneficial to industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a supported copper-based catalyst and its preparation and application in preparing aniline by hydrogenating nitrobenzene. Background Art

[0002] Aniline occupies a huge share in the organic chemical industry market and is an important synthetic unit for organic chemicals such as medicines, dyes, and pesticides. Selective reduction using nitrobenzene as a raw material is the best route for preparing aniline. Using alkaline metals as reducing agents can achieve selective reduction of nitrobenzene to prepare aniline, but the large amount of iron oxide produced as a byproduct exceeds market demand, making the economic cost of this process route too high.

[0003] At present, hydrogen, as the most commonly used and cheapest industrial reducing gas, is used for the selective hydrogenation of nitrobenzene to produce aniline. The catalyst systems for the hydrogenation of nitrobenzene to produce aniline mainly include supported noble metal systems such as Pd, Pt, Au, and supported non-noble metal systems such as Ni, Fe, and Co. The noble metal catalysts show high activity in this hydrogenation process, but their strong hydrogenation ability makes them prone to over-hydrogenation and produce supersaturated products during the hydrogenation process.

[0004] Patent CN108295843A discloses a method for preparing a three-dimensional graphene-loaded nano Pd catalyst by a soft film plate method, wherein a certain amount of graphite oxide is weighed and added to an emulsion system of deionized water, ethanol and cyclohexane, the graphite oxide concentration is 0.5-4 mg / mL, and then ultrasonicated at room temperature for 5-20 min to obtain a dispersed graphene oxide emulsion; 60-100 mg of ascorbic acid is added to the emulsion obtained in the step, and the mixed solution is treated in a 60-90°C water bath for 0.25-2 h; then 0.3-1 mL of a PdCl2 aqueous solution with a concentration of 0.02 mol / L is added and stirred in an oil bath; the resulting mixture is centrifuged, washed with deionized water and ethanol in sequence, and vacuum dried to obtain the catalyst. In this method, graphite oxide is used as a carrier, and ascorbic acid and precious metal Pt are used at the same time, which makes its industrial application cost too high and production limited. At present, industrially developed non-precious metal catalysts including Ni sulfide, Cu, Mn, Fe composite catalysts, etc. all need to operate above 300°C. Excessively high reaction temperature brings about problems such as high energy consumption and poor catalyst stability.

[0005] In summary, in the process of preparing aniline by hydrogenation of nitrobenzene, there are generally problems such as high catalyst activity but poor selectivity, high catalyst cost and low reaction activity at low temperatures. Therefore, it is of great significance to develop a high-activity, low-cost catalyst preparation method. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of low catalyst activity and high cost in the process of preparing aniline by hydrogenating nitrobenzene, and to provide a cheap and easy-to-prepare supported copper-based catalyst with high activity and selectivity for catalyzing the hydrogenation of nitrobenzene.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme:

[0008] The present invention provides a method for preparing a supported copper-based catalyst, comprising the following steps:

[0009] (1) dissolving a copper salt in water to obtain a copper salt solution;

[0010] (2) impregnating an equal volume of a copper salt solution onto a metal oxide A, and drying the solid in a constant temperature oven at 40-120° C. for 4-24 hours; calcining the dried solid in a muffle furnace at 300-500° C. (preferably 380-420° C., more preferably 400-410° C.) for 2-12 hours; and reducing the solid in a hydrogen atmosphere at 200-400° C. (preferably 280-320° C., more preferably 290-300° C.) for 1-6 hours (preferably 1.5-2 hours);

[0011] (3) placing the obtained solid in an organic solvent and adding another metal oxide B; heating the mixed solution to 100-170° C. (preferably 120-150° C., more preferably 130-140° C.) for 1-24 hours; and centrifuging and washing to obtain a supported copper-based catalyst.

[0012] The mass ratio of copper to metal oxide A in the prepared supported copper-based catalyst is 1-10% (preferably 1.5-3%, more preferably 1.9-2.1%); the mass ratio of metal oxide A to metal oxide B is 0.1-10, preferably 0.2-2, more preferably 0.8-1.2;

[0013] The copper salt is one or more of copper nitrate, copper sulfate, copper chloride and copper acetate;

[0014] The molecular formula of copper nitrate is Cu(NO3)2·xH2O (x=0, 3 or 6), the molecular formula of copper sulfate is CuSO4·yH2O (x=0, 1, 3 or 5), the molecular formula of copper chloride is CuCl2·zH2O (x=0 or 2), and the molecular formula of copper acetate is Cu(CH3COO)2·wH2O (x=0 or 1);

[0015] The metal oxide A is one or two or more of Al2O3, SiO2 or TiO2 (preferably TiO2); the metal oxide B is one or two or more of Nb2O5, CeO2 or ZrO2 (preferably CeO2); in the metal oxide, the mass ratio of the metal oxide A to the metal oxide B is 0.1-10 (preferably 0.2-2);

[0016] The organic solvent is one or two or more of methanol, ethanol, hexane, heptane, octane, toluene, xylene, trimethylbenzene, ethylbenzene, acetonitrile, and 1,4-dioxane;

[0017] The hydrogen-containing atmosphere is hydrogen, or a mixture of hydrogen and an inert gas; the inert gas includes one or more of nitrogen, argon, and helium; the volume fraction of hydrogen in the hydrogen-containing atmosphere is 1-100%;

[0018] The present invention provides application of a supported copper-based catalyst prepared by the preparation method in nitrobenzene hydrogenation.

[0019] The reaction specifically comprises placing the prepared supported copper-based catalyst in a high-pressure reactor, adding an organic solvent and nitrobenzene, adding a reducing agent, and promoting the reaction under heating conditions.

[0020] The organic solvent is one or two or more of methanol, ethanol, toluene, xylene, 1,4-dioxane, and cyclohexane; the reducing agent is H2; the heating condition temperature is 100-160°C, preferably 120-150°C, more preferably 130-140°C; the time is 0.5-10 hours, preferably 1-5 hours, more preferably 2-3 hours;

[0021] The H2 has a pressure of 0.2-5 MPa;

[0022] The preparation method disclosed in the present invention can realize the migration of copper species between different metal oxides at low temperature, and obtain supported copper-based catalysts with different dispersions and electronic states. The present invention provides the application of the prepared supported copper-based catalyst in nitrobenzene hydrogenation, which has high activity and high selectivity. The preparation method is simple, low in cost, and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : High magnification transmission electron microscope image of the supported copper-based catalyst Cu / TiO2-CeO2-1 obtained in Example 1 and the corresponding EDS line scan element analysis; the results show that part of Cu migrated from TiO2 to CeO2;

[0024] Figure 2: Transmission electron microscope image of the supported copper-based catalyst Cu / TiO2-CeO2-1 obtained in Example 1; the size range of CeO2 is 5-10 nanometers, and the size range of TiO2 is 30-60 nanometers, and the results show that CeO2 is in close contact with TiO2;

[0025] Figure 3 : Transmission electron microscope image of the supported copper-based catalyst Cu / TiO2-CeO2-2 obtained in Example 2; the size range of CeO2 is 5-10 nanometers, and the size range of TiO2 is 30-60 nanometers. The results show that CeO2 is in close contact with TiO2. DETAILED DESCRIPTION

[0026] To further illustrate the present invention, the detailed preparation process is described below in conjunction with specific embodiments, but this is only used for detailed description of the present invention and cannot be regarded as a limitation on the protection scope of the present invention.

[0027] Example 1

[0028] Preparation of Cu / TiO2-CeO2-1:

[0029] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0030] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0031] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0032] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1;

[0033] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions of: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 99.8%, and the selectivity of aniline was 99.9%.

[0034] Example 2

[0035] Preparation of Cu / TiO2-CeO2-2:

[0036] (1) Dissolve 0.456 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0037] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 52 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0038] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0039] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 4%, and a mass ratio of TiO2-R to cerium oxide of 1:1;

[0040] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 102 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 99.9% and the selectivity of aniline was 97.0%.

[0041] Example 3

[0042] Preparation of Cu / TiO2-CeO2-3:

[0043] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0044] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0045] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 100 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0046] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:2;

[0047] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 151 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 92.2%, and the selectivity of aniline was 99.9%.

[0048] Example 4

[0049] Preparation of Cu / TiO2-CeO2-4:

[0050] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0051] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0052] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 100 mg cerium oxide, and filling the autoclave with 2 MPaAr; heating to 140° C. and maintaining for 3 hours;

[0053] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:2;

[0054] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 82.6%, and the selectivity of aniline was 99.9%.

[0055] Example 5

[0056] Preparation of Cu / TiO2-CeO2-5:

[0057] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0058] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 20 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0059] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0060] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1;

[0061] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 93.6%, and the selectivity of aniline was 99.9%.

[0062] Example 6

[0063] Preparation of Cu / TiO2-CeO2-6:

[0064] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0065] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 280° C. for 2 hours to obtain a reduced sample;

[0066] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0067] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1;

[0068] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions of: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 94.2%, and the selectivity of aniline was 99.7%.

[0069] Example 7

[0070] Preparation of Cu / TiO2-ZrO2:

[0071] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0072] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0073] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg zirconium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0074] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to cerium oxide of 2%, and a mass ratio of TiO2-R to zirconium oxide of 1:1;

[0075] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 90.8%, and the selectivity of aniline was 99.9%.

[0076] Comparative Example 1

[0077] Preparation of Cu / TiO2-CeO2-D1:

[0078] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0079] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours;

[0080] (3) Weigh 51 mg of the sample calcined in step (2) and place it in a 20 mL autoclave, add 2 mL of toluene; then add 50 mg of cerium oxide, fill the autoclave with 2 MPa of H2; heat to 140°C and maintain for 3 hours;

[0081] (4) The treated material obtained in step (3) is centrifuged, the solid is washed, and dried (vacuum dried at 100° C. for 6 hours) to obtain a supported copper-based catalyst with a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1.

[0082] The catalyst prepared as above was used to evaluate the catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 23.2%, and the selectivity of aniline was 66.8%.

[0083] Comparative Example 2

[0084] Preparation of Cu / CeO2-D2:

[0085] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.1 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of cerium oxide while stirring until it reaches a saturated adsorption amount (i.e., equal volume immersion), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0086] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining it in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours;

[0087] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; filling the autoclave with 2 MPa H2; raising the temperature to 140°C and maintaining for 3 hours;

[0088] (4) The treated material obtained in step (3) is centrifuged, the solid is washed, and dried (vacuum dried at 100° C. for 6 hours) to obtain a supported copper-based catalyst with a copper to cerium oxide mass ratio of 2%.

[0089] The catalyst prepared as above was used to evaluate the catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 51 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 46.2%, and the selectivity of aniline was 15.6%.

[0090] Comparative Example 3

[0091] Preparation of Cu / TiO2-CeO2-D3:

[0092] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0093] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0094] (3) placing the reduced sample in step (2) in a 20 mL autoclave, adding 2 mL of water; then adding 50 mg of cerium oxide, and filling the autoclave with 2 MPa of H2; raising the temperature to 140°C and maintaining for 3 hours;

[0095] (4) The treated material obtained in step (3) is centrifuged, the solid is washed, and dried (vacuum dried at 100° C. for 6 hours) to obtain a supported copper-based catalyst with a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1.

[0096] The catalyst prepared as above was used to evaluate the catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 100 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 48.8%, and the selectivity of aniline was 69.5%.

[0097] Comparative Example 4

[0098] Preparation of Cu / TiO2-CeO2-D4:

[0099] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0100] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0101] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 1 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0102] (4) The treated material obtained in step (3) is centrifuged, the solid is washed, and dried (vacuum dried at 100° C. for 6 hours) to obtain a supported copper-based catalyst with a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:0.02.

[0103] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 52 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 46.5%, and the selectivity of aniline was 52.8%.

[0104] Comparative Example 5

[0105] Preparation of Cu / TiO2-CeO2-D5:

[0106] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.6 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of rutile titanium oxide (TiO2-R) carrier, stirring while adding until it reaches saturated adsorption (i.e., equal volume impregnation), at which point the prepared solution is just completely absorbed and the metal ions are completely loaded onto the carrier, thereby obtaining a sample;

[0107] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0108] (3) placing the sample reduced in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 800 mg cerium oxide, and filling the autoclave with 2 MPa H2; heating to 140°C and maintaining for 3 hours;

[0109] (4) The treated material obtained in step (3) is centrifuged, the solid is washed, and dried (vacuum dried at 100° C. for 6 hours) to obtain a supported copper-based catalyst with a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:16.

[0110] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 851 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 56.2%, and the selectivity of aniline was 24.8%.

[0111] Comparative Example 6

[0112] Preparation of Cu / CeO2-TiO2:

[0113] (1) Dissolve 0.228 g of copper nitrate trihydrate in 1.1 mL of ultrapure water until it is completely dissolved to form a uniform solution; add the solution dropwise onto 3 g of a cerium oxide support while stirring until the saturated adsorption capacity (i.e., equal volume impregnation) is reached, at which point the prepared solution is completely absorbed and the metal ions are completely loaded onto the support, thereby obtaining a sample;

[0114] (2) drying the sample obtained in step (1) in a 100° C. forced air oven for 12 hours, and then calcining the sample in a muffle furnace at 400° C. for 4 hours; weighing 51 mg of the obtained solid and reducing it in a 30 vol.% H2 / N2 mixed gas at 300° C. for 2 hours to obtain a reduced sample;

[0115] (3) placing the reduced sample in step (2) in a 20 mL autoclave, adding 2 mL toluene; then adding 50 mg rutile titanium oxide (TiO2-R), and filling the autoclave with 2 MPa H2; heating to 140° C. and maintaining for 3 hours;

[0116] (4) centrifuging the treated material obtained in step (3), washing the solid, and drying (vacuum drying at 100° C. for 6 hours) to obtain a supported copper-based catalyst having a mass ratio of copper to TiO2-R of 2%, and a mass ratio of TiO2-R to cerium oxide of 1:1;

[0117] The catalyst prepared as above was used for the evaluation of catalytic hydrogenation of nitrobenzene in a high-pressure reactor. Under the reaction conditions: catalyst dosage 101 mg, nitrobenzene 90 mg, toluene 2 mL, H2 2 MPa, reaction temperature 140°C, reaction time 3 hours, the conversion rate of nitrobenzene was 41.8%, and the selectivity of aniline was 56.8%.

Claims

1. A method for preparing a supported copper-based catalyst, characterized in that: The steps include: 1) dissolving copper salt in water to obtain a copper salt solution; 2) impregnating an equal volume or excess volume of a copper salt solution onto a metal oxide A, and drying in a constant temperature oven at 40-120° C. for 4-24 hours; calcining the dried solid in a muffle furnace at 300-500° C. (preferably 380-420° C., more preferably 400-410° C.) for 2-12 hours; and reducing the solid in a hydrogen-containing atmosphere at 200-400° C. (preferably 280-320° C., more preferably 290-300° C.) for 1-6 hours to obtain a solid; 3) placing the solid obtained in step 2) in an organic solvent and adding another metal oxide B; heating the mixed solution to 100-170°C (preferably 120-150°C, more preferably 130-140°C) and maintaining for 1-24 hours; separating the solid and the liquid, and obtaining the solid as a supported copper-based catalyst; the metal oxide A is one or two or more of Al2O3, SiO2 or TiO2; the metal oxide B is one or two or more of Nb2O5, CeO2 or ZrO2.

2. The preparation method according to claim 1, characterized in that: The mass ratio of copper to metal oxide A in the prepared supported copper-based catalyst is 1-10%, preferably 1.5-3%, more preferably 1.9-2.1%; The mass ratio of metal oxide A to metal oxide B is 0.1-10, preferably 0.2-2, more preferably 0.8-1.

2.

3. The preparation method according to claim 1, characterized in that: The organic solvent is one or two or more of methanol, ethanol, hexane, heptane, octane, toluene, xylene, trimethylbenzene, ethylbenzene, acetonitrile, and 1,4-dioxane; The volume mass ratio of the organic solvent to the metal oxide B is 1-3 mL of organic solvent: 10-250 mg of metal oxide B, preferably 1.8-2.0 mL of organic solvent: 40-50 mg of metal oxide B.

4. The preparation method according to claim 1, characterized in that: The copper salt is one or more of copper nitrate, copper sulfate, copper chloride and copper acetate; The molecular formula of the copper nitrate is Cu(NO3)2·xH2O (x=0, 3 or 6), the molecular formula of the copper sulfate is CuSO4·yH2O (x=0, 1, 3 or 5), the molecular formula of the copper chloride is CuCl2·zH2O (x=0 or 2) and the molecular formula is Cu(CH3COO)2·wH2O (x=0 or 1); The solid-liquid separation method is centrifugation, and after centrifugation, the solid is collected and washed to obtain a supported copper-based catalyst.

5. The method for preparing a supported copper-based catalyst according to claim 1, wherein: The hydrogen-containing atmosphere is hydrogen, or a mixture of hydrogen and an inert gas; the inert gas includes one or more of nitrogen, argon, and helium; the hydrogen volume fraction in the hydrogen-containing atmosphere is 1-100%; The heating treatment atmosphere in step 3) is one or more of hydrogen, nitrogen, argon and helium.

6. A supported copper-based catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the supported copper-based catalyst according to claim 6 in catalytic hydrogenation of nitrobenzene.

8. The use according to claim 7, characterized in that The application is specifically as follows: placing the supported copper-based catalyst in a high-pressure reactor, adding an organic solvent and nitrobenzene, adding a reducing agent, and promoting the reaction under heating conditions.

9. The use according to claim 8, characterized in that: The organic solvent is one or two or more of methanol, ethanol, toluene, xylene, 1,4-dioxane, and cyclohexane; The reducing agent is H2, and its pressure is 0.2-5MPa, preferably 1-3MPa, and more preferably 1.8-2MPa.

10. The use according to claim 8, characterized in that: The heating conditions are as follows: the temperature is 100-160° C., preferably 120-150° C., more preferably 130-140° C.; the time is 0.5-10 hours, preferably 1-5 hours, more preferably 2-3 hours.

Citation Information

Patent Citations

  • Method for preparing three-dimensional graphene supported nano Pd catalyst with soft template method and application of catalyst to nitrobenzene hydrogenation

    CN108295843A

  • Method for preparing benzhydrol by hydrogenation of benzophenone

    CN111233626A

  • Supported cuprous oxide nano material and preparation method thereof

    CN115608358A

  • Preparation and application of modified cerium oxide carrier loaded Pt-based catalyst

    CN116603523A

  • Nitrobenzene hydrogenation catalyst with high aniline yield rate

    CN1367040A